Genomic detection of new yeast pre-mRNA 3'-end-processing signals. - Graber, J H (1999)
To investigate Saccharomyces cerevisiae 3'-end-processing signals, a set of 1352 unique pre-mRNA 3'-end-processing sites, corresponding to 861 different genes, was identified by alignment of expressed sequence tag sequences with the complete yeast genome. Nucleotide word frequencies in the vicinity of the cleavage sites were analyzed to reveal the signal element features. In addition to previously recognized processing signals, two previously uncharacterized components of the 3'-end-processing signal sequence were discovered, specifically a predominance of U-rich sequences located on either side of the cleavage site. One of these, the downstream U-rich signal, provides a further link between the 3'-end-processing mechanisms of yeast and higher eukaryotes. Analysis of the complete set of 3'-end-processing sites by means of a discrimination function supports a 'contextual' model in which the sum total effectiveness of the signals in all four elements determines whether or not processing occurs.